Analisis Faktor Faktor Terjadinya Penyimpangan Hubungan Seksual di Kelurahan Rimbo Pengadang Kabupaten Lebong - Dewi Ayu Wahyuni An Nur (Yayasan Darusssalam Bengkulu, 2025)
This study was conducted with the aim of obtaining information regarding the causes of sexual deviation and related to PAI. In addition, it also aims to determine the factors of sexual behavioral deviation. The researcher used a qualitative research method, a case study type, the subjects of this study were perpetrators of sexual deviation and their victims in Rimbo Pengadang Village, Rimbo Pengadang District, Lebong Regency. Furthermore, the informants in this study consisted of the police, residents, community leaders, religious leaders, subjects and close friends of the subjects. Data collection in this study used non-participant observation techniques, open interviews, checking the validity of the data in this study was using triangulation techniques and sources. Data were analyzed qualitatively. Based on the presentation of the research results, factors were found that sexual relations occurred in Rimbo Pengadang Village, Lebong Regency. Caused by addiction to watching pornographic films, having been a victim of sodomy, lack of religious education and sexual education. The results of the study found that From the results that the researcher found that, from the KUA, Religious counselors and even from local government cadres. They have tried to implement socialization about sexual education in the village office and in religious studies delivered by members of the Integrated Health Post (Posyandu), religious instructors. Forms of deviant sexual behavior and its relation to the implementation of Islamic Religious Education in Rimbo Pengadang Village, Rimbo Pengadang District, Lebong Regency, it was found that the forms of deviant behavior when related to Islamic religious education have been explained by religious figures and religious instructors about sex education given during religious studies and community socialization and even when Posyandu has also been delivered about knowledge of sexual education.